ANALISIS PENGARUH JUMLAH UANG BEREDAR, SUKU BUNGA SBI, NILAI TUKAR TERHADAP TINGKAT INFLASI - Heru Perlambang (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2010)
Inflation is one of the effects of a prolonged economic crisis that hit thecountry. Inflation is a situation where there are price rises sharply (Absolute)which continues over a period of time. The purpose of this study analyzes themonetary policy conducted by Bank Indonesia and its influence as the moneysupply, interest rates and exchange rates SBI (IDR / USD) of the inflation rate.The method used is multiple linear regression based on test results indicateavariable effect on money supply, interest rate of SBI, and the exchange rate(Rp / USD) in 2004 to 2009. By using eviews 4.0 software obtained from theresults of research following the money supply and exchange rate (Rp/USD)had no significant effect on inflation while the interest rate (SBI) have asignificant effect on inflation.